Investigation of The Relationship Between Preschoolers’ Competition Styles, Anxiety Levels and Their Parents’ Parental Styles - Yıldız, Songül; Ramazan Sak (Southeast Asia Early Childhood Journal, 2024)
The aim of this study is to investigate the relationship between preschoolers’ competition styles, anxiety levels, and their parents’ parental styles. The sample of the study consists of 400 preschool children and their parents. The Demographic Information Form, Parenting Style Scale, Preschool Competition Questionnaire, and Anxiety Scale for Preschool Children were used as data collection tools in this quantitative survey-based study. As a result of the research, significant negative correlation was found between the task-oriented competition style of preschool children and their generalized anxiety level, separation anxiety, specific phobia anxiety and total anxiety level. A negative significant relationship was found in the other-referenced competition and separation anxiety sub-dimension. A negative significant correlation was found between the maintenance of dominance hierarchy style and specific phobia anxiety and total anxiety. A negative significant relationship was found between democratic parenting style and social anxiety sub-dimension, and total anxiety level. A positive significant relationship was found between parents' authoritarian and overprotective parenting styles and all sub-dimensions of anxiety scale and total anxiety level. There was no significant relationship between permissive parenting style and any of the sub-dimensions of the anxiety scale and total of the anxiety scale. A positive significant relationship was found between democratic parenting style and task-oriented competition style.